Probiotic Potential of Lactic Acid Bacteria Isolated from Local Dairy Products of Kohat, Pakistan - Jehan, Samina; Rehman, Hazir; Qasim, Muhammad; Tabassum, Anum (PSM Microbiology, 2019)
Probiotics are living microbes which upon ingestion in appropriate number have beneficial effects on host’s health. Dairy products are the potential source of Lactic acid bacteria (LAB). In the present study, LAB was isolated from different local dairy products from Kohat, Pakistan. Out of 67 isolates from 52 samples of dairy products, 30 isolates were identified as LAB on the basis of their morphological and biochemical profile. Probiotic properties of the isolates were investigated by determination of their antibacterial activities and tolerance to bile salt and pH. Antimicrobial activity of cell-free supernatant of LAB isolates was determined against indicator bacteria Salmonella typhi, Escherichia coli, and Staphylococcus aureus by using agar well diffusion method. Maximum zone of inhibition of 15.33±0.5 mm against E. coli by C1Bt isolate, 22±1 mm against S. typhi by B4M isolate and 19.33±0.5 mm against S. aureus by C1Bt isolate was observed. Six of the isolates with good antibacterial activity were subjected to bile tolerance and pH tolerance. The selected isolates showed tolerance against different bile concentrations and pH. C1Bt isolate showed highest tolerance to 0.5% bile concentration, while B4M isolate showed highest tolerance against acidic and alkaline pH.